Molecular characterization of binding of calcium and carbohydrates by an early activation antigen of lymphocytes CD69 - Pavlícek, Jirí; Sopko, Bruno; Ettrich, Rüdiger; Kopecký, Vladimír; Baumruk, Vladimír; Man, Petr; Havlícek, Vladimír; Vrbacký, Marek; Martínková, Ludmila; Kren, Vladimír; Pospísil, Miloslav; Bezouska, Karel (Biochemistry, 2003)
CD69 is the earliest leukocyte activation antigen playing a pivotal role in cellular signaling. Here, we show that a globular C-terminal domain of CD69 belonging to C-type lectins binds calcium through Asp 171, Glu 185, and Glu 187 with K(d) approximately 54 microM. Closure of the calcium-binding site results in a conformational shift of Thr 107 and Lys 172. Interestingly, structural changes in all of these amino acids lead to the formation of high-affinity binding sites for N-acetyl-D-glucosamine. Similarly, a structural change in Glu 185 and Glu 187 contributes to a high-affinity site for N-acetyl-D-galactosamine. Site-directed mutagenesis and molecular modeling allowed us to describe the structural details of binding sites for both carbohydrates. These studies explain the importance of calcium for recognition of carbohydrates by CD69 and provide an important paradigm for the role of weak interactions in the immune system.
Keywords: kinetika; Molecular Sequence Data; sekvence aminokyselin; Models, Molecular; Antigens, Differentiation, T-Lymphocyte; Lymphocytes; polymerázová řetězová reakce; Polymerase Chain Reaction; vápník; Lectins, C-Type; DNA primery; Mutagenesis, Site-Directed; mutace; Acetylglucosamine; lymfocyty; lektiny typu C; diferenciační antigeny T-lymfocytů; Calcium; mutageneze cílená; Escherichia coli; molekulární modely; Mutation; Humans; Amino Acid Sequence; Antigens, CD; Kinetics; sbalování proteinů; molekulární sekvence - údaje; DNA Primers; sekvenční homologie aminokyselin; Protein Folding; CD antigeny; lidé; Sequence Homology, Amino Acid; acetylglukosamin